Synthesis, crystallographic studies, high resolution mass spectrometric analyses and antibacterial assays of silver(I) complexes with sulfisoxazole and sulfadimethoxine. (10th January 2017) - Fiori, Ana Thereza M.; Nakahata, Douglas H.; Cuin, Alexandre; Lustri, Wilton R.; Corbi, Pedro P.
Graphical abstract: Molecular view of the Ag–SIZ and Ag–SDMX dimers obtained by X-ray powder diffraction. Silver is pink colored, while carbon, hydrogen, nitrogen, oxygen and sulfur are black, white, blue, red and yellow, respectively. Abstract: The present work describes the synthesis, structural characterization and antibacterial assays of two silver(I) complexes with the sulfa drugs sulfisoxazole (SIZH) and sulfadimethoxine (SDMXH). Chemical analyses and high resolution mass spectrometric studies led to 1:1 metal/ligand compositions, suggesting the minimal formulas AgC11 H12 O3 N3 S·H2 O for Ag–SIZ and AgC12 H13 O4 N4 S for Ag–SDMX. Infrared and solution state NMR spectroscopic measurements indicated ligand coordination to Ag(I) by the nitrogen atoms of the SO2 N and NH2 groups in Ag–SIZ, whereas for Ag–SDMX the coordination of the ligand to Ag(I) occurs by the SO2 N group and one of the nitrogen atoms of the pyrimidine ring. The proposed coordination modes were confirmed by X-ray diffraction studies and showed the formation of dimeric structures in both cases. The Ag–SDMX complex shows the classical bridging mode of coordination, in which the silver ions bridge between the nitrogen atom of the sulfonamide group of one ligand and the nitrogen atom of the pyrimidine ring of the second ligand, while for the Ag–SIZ complex coordination occurs by the nitrogen atoms of the NH2 and SO2 N groups. Antibacterial assays indicated that Ag–SIZ and Ag–SDMX complexes are effective against Gram-negative ( Escherichia coli and Pseudomonas aeruginosa ) and Gram-positive ( Staphylococcus aureus ) bacterial strains, being the Ag–SDMX complex more active than the Ag–SIZ one. These results are an indicative that the ligand structures and dissimilar coordination modes of the sulfonamides may be associated to the antibacterial activities of the complexes.